KAJIAN NOVEL ARUNIKA TERAKHIR KARYA IPUL SAE MENGGUNAKAN PENDEKATAN ENKLITIK - Nurunnisa Syifaul Fadhilah; Kuswara; Dedi Irawan (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research is motivated by the imbalance of literary appreciation, literary appreciation is only focused on literary studies using an objective approach that considers literary works as something that stands alone so that it seems incomplete. Through an enclitic approach, literary appreciation in this study uses two approaches that are used simultaneously, combining objective and expressive approaches. This study aims to describe the novel Arunika Terakhir by Ipul Sae, a description of the author's sociology, the influence of the author's sociological aspects on intrinsic elements, and the procedure for applying the enclitic approach in literary studies. The method used is a descriptive method with a qualitative approach. The research technique uses text analysis techniques and interviews. Based on the results of the interview, it can be seen that Ipul Sae is someone who is active in the fields of environment, education, literacy, social, and art. The author is from Sumeadang Regency, in 2016 the author established a reading garden called Panti Baca Ceria. The first book is entitled Kata Benda and the second book is entitled Arunika Terakhir. This novel is interesting to study because it is a fiction genre and it reflects the imagination, creativity, and reality experienced by the author. In the novel Arunika Terakhir by Ipul Sae, the issues raised in the story are the struggle to save the environment from human greed, the lives of humans and other creatures in a coexistent world, and human awareness of the environment in which they live. The main character named Varsha Eka Saptarangi, is set in 2080 in a city called Medalion. The application of an enclitic approach by linking the first data in the form of the author's sociology and the second data in the form of intrinsic elements of the novel Arunika Terakhir by Ipul Sae so that the relationship between the author's background, who is a man from Sumedang, chooses the name of the character, character of the character, setting of place, the theme of the story, and how to resolve the conflict in the novel. The author works in the environmental field so that it affects the theme of the story raised, and the message conveyed. The author brings up traditional values ​​that are still embraced by the Sundanese people related to the author's passion for traditional arts.